Long-term survival of kidney grafts in lupus nephritis: a Mexican cohort. (July 2018) - Ramirez-Sandoval, J C; Chavez-Chavez, H; Wagner, M; Vega-Vega, O; Morales-Buenrostro, L E; Correa-Rotter, R
Kidney transplant for patients with lupus nephritis (LN) has satisfactory outcomes in studies with short-term or mid-term follow up. Nevertheless, information about long-term outcomes is scarce. We performed a retrospective matched-pair cohort study in 74 LN recipients compared with 148 non-LN controls matched by age, sex, immunosuppressive treatment, human leukocyte antigen (HLA) matches, and transplant period in order to evaluate long-term outcomes of kidney transplant in LN recipients. Matched pairs were predominantly females (83%), median age at transplant surgery of 32 years (interquartile range 23–38 years), and 66% received a graft from a living related donor. Among LN recipients, 5-, 10-, 15-, and 20-year graft survival was 81%, 79%, 57% and 51%, respectively, and it was similar to that observed in controls (89%, 78%, 64%, and 56%, respectively). Graft loss (27% vs. 21%, p  = 0.24) and overall survival ( p  = 0.15) were not different between LN recipients and controls. Also, there was no difference in episodes of immunological rejection, thrombosis, or infection. Only six LN recipients had biopsy-proven lupus recurrence and three of them had graft loss. In a cohort with a long follow up of kidney transplant recipients, LN recipients had similar long-term graft survival and overall outcomes compared with non-lupus recipients when predictors are matched between groups.